Informing employees in small and medium-sized firms about training: Results of a randomized field experiment - Gerard J. van den Berg; Christine Dauth; Pia Homrighausen; Gesine Stephan (Economic Inquiry, 2022)
We mailed brochures to 10,000 randomly chosen employed German workers who were eligible for a subsidized occupational training program called WeGebAU, informing them about the importance of skills-upgrading training in general and about WeGebAU in particular. Using survey and register data, we estimate effects of the informational brochure on awareness of the program, on take-up of WeGebAU and other training, and on subsequent employment. The brochure more than doubles awareness of the program. There are no effects on WeGebAU take-up, but participation in other (unsubsidized) training increases among employees aged under 45. Short-term labor market outcomes are not affected.
Keywords: 330; employment; information treatment; randomized controlled trial; skills; training subsidies; wages